Tirzepatide against obesity and insulin-resistance: pathophysiological aspects and clinical evidence - Corrao, Salvatore; Pollicino, Chiara; Maggio, Dalila; Torres, Alessandra; Argano, Christiano (Frontiers in Endocrinology, 2024)
Obesity is a chronic, multifactorial disease in which accumulated excess body fat has a negative impact on health. Obesity continues to rise among the general population, resulting in an epidemic that shows no significant signs of decline. It is directly involved in the development of cardiovascular disease risk factors such as arterial hypertension, ischemic heart disease or stroke, heart failure, and peripheral arterial disease, producing global morbidity and mortality. Mainly, abdominal obesity represents a crucial cardiovascular risk factor and the most frequent component of metabolic syndrome. Recent evidence showed that Tirzepatide (TZP), a new drug including dual Glucagon Like Peptide 1 (GLP-1) and Glucose-dependent Insulinotropic Polypeptide (GIP) receptor agonism, is effective in subjects with type 2 diabetes (T2D), lowering glycated haemoglobin (HbA1c) and body weight (BW), and in adults with obesity and overweight who did not have T2D. This review discusses the pathophysiological mechanisms and clinical aspects of TZP in treating obesity.